2019
DOI: 10.14411/eje.2019.003
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D1 versus ecdysteroids: Growth effects on cell regeneration and malignant growth in insects are similar to those in humans

Abstract: Polyhydroxylated derivatives of 6-keto,7-dehydrocholesterol (ecdysteroids) are common constituents of various plants. In 1965, they were accidentally discovered in the search for the insect moulting hormone. These biologically important natural compounds are neither insect hormones nor inducers of insect ecdysis. Due to their strong anabolic, vitamin D-like effects in insects, domestic animals and humans, I propose the use of the arbitrary term vitamin D 1 . The present paper describes the effects of vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
4
0
2
Order By: Relevance
“…IGF‐BP, present in extracellular fluids, was reported to enhance IGF‐I bioactivity (Sara & Hall, 1990). Sláma (2019) reported that ecdysteroids have a strong anabolic effect and act like vitamin D in insects and animals. Insect growth depends on the periodic replacement of the exoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…IGF‐BP, present in extracellular fluids, was reported to enhance IGF‐I bioactivity (Sara & Hall, 1990). Sláma (2019) reported that ecdysteroids have a strong anabolic effect and act like vitamin D in insects and animals. Insect growth depends on the periodic replacement of the exoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…During metamorphosis the titer of ecdysteroids rises to high concentrations and contributes to the remodeling of the body, while the titer of JHs falls to zero. Recently, Sláma et al (54) has put forward the concept "vitamin D 1 " for presenting the water-soluble anabolic steroid of plant origin (55) that also displays "molting hormone" activity in insects and crustaceans. This real vitamin D occurs in high concentrations in some plants.…”
Section: Discussionmentioning
confidence: 99%
“…The stem cells may need growth factors, but their identity remains largely unclear. Yet, an interesting novel insight has recently been advanced by Sláma (54). He suggested that the molting hormone of insects and other arthropods, namely 20-hydroxyecdysone the titer of which is high during metamorphosis, is a water-soluble anabolic steroid.…”
Section: Insects Manage To Survive Situations Of Massive Programmed Cmentioning
confidence: 99%
“…6,7 Additionally, numerous food sources and plants employed in traditional medicine have been identified to contain significant amounts of ECDY. [8][9][10][11] In two recent studies, it was demonstrated that after the ingestion of regular meals containing, for example, spinach, considerable concentrations (up to 700 ng/mL) of ECDY were detected in urine. 12,13 Therefore, the presence of ECDY in an athlete's urine alone cannot prove an illicit administration, and further studies seemed warranted.…”
Section: Introductionmentioning
confidence: 99%